Karakteristik Sampah Plastik di Laguna Segara Anakan Cilacap - Nurito, Nurito; Andriyono, Sapto; Hendrayana, Hendrayana; Husni, Iqbal Ali; Hidayat, Rizqi Rizaldi; Rofiq Ulinuha, Mohamad; Hidayati, Nuning Vita (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Nurito N, Andriyono S, Hendrayana H, Husli IA, Hidayat RR, Andriyono S, Ulinuha MR, Hidayati NV. Characteristics of plastic waste in Cilacap segara anakan lagoon. ini. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 293-301. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Plastic litter degrade very slowly in the natural environment. The different characteristics of plastic waste are one of the determining factors in the decomposition process. This study aimed to investigate the type, abundance and characteristics plastic waste in Segara Anakan Lagoon. Plastic waste was taken from Segara Anakan Lagoon on August, 2020 using survey method. Sample was collected from 1x1 meter transect. Analysis of the data used is descriptive analysis. The results showed that we found 7 types of plastics waste, i.e. PET, HDPE, PVC, LDPE, PP, PS, and OTHER. The highest plastic waste abundance was found in station 2 (82,67 items/m2), and the lowest was in station 9 (1,67 items/m2). PP is the dominant type of plastic with a total of 839 items (71.5%) followed by LDPE with a total of 189 items (16.1%), while PVC and PS were found in lowest number, with each of them 6 items (0.5%). The characteristics of plastic waste in Segara Anakan based on the type of plastic waste at station 2 have different types with other stations and the differences are clearly illustrated.